The Effectiveness of Recorded Materials in EFL Class - Bastola, Laxmi Prasad (Journal of NELTA Surkhet, 2018)
In the era of globalization, it is very necessary to know about the recorded materials while teaching English as a second language. It is needless to say that the recorded materials are the boon of science and technology which has made easier the formal learning process. Till now many English teacher has been ignoring the power of recorded materials in language teaching specially, in the secondary level of school. Obviously, English language teaching is difficult in the context of Nepal but those materials related to recorded make the classroom more lively. As a result the learning becomes the easier process. This paper concludes that the recorded materials are very useful to develop the listening comprehension of the learners of Secondary Level School. Journal of NELTA Surkhet, Vol. 5 January, 2018, Page: 49-55